Everyday practices of domination and resistance in the Turkish mainstream media - Ünal, Elif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This thesis aims to find an answer to the following question: How does domination work inside Turkish mainstream media outlets? Although the neoliberal transformation and the establishment of a competitive authoritarian regime under the Justice and Development Party (AKP) rule provide us a macro-level understanding, they do not explain the functioning of domination on a daily basis. The thesis uses the ‘everyday resistance’ theory to capture the dynamic and dialectical relationship between micro-level everyday practices of domination and resistance in the media space. The thesis claims that the neoliberal media structure leads to the precarization of the journalists which makes them more vulnerable to the domination of government. In order for the domination to work in the media arena, the government does not need total control of the minds of the journalists as long as it forces journalists to seek covert forms of resistance rather than open confrontation. Since these covert forms are not adequate to challenge the system, even journalists’ resistance strategies can become tools for strengthening the domination of media arena.
Keywords: Mass media -- Turkey.; Press and politics -- Turkey.